A wandering archive – a nuanced creative enactment of GLBT histories. Issue 5 (2nd September 2016) - Charman, Karen
Abstract: This article examines performativity of gay, lesbian, bisexual and transgender (GLBT) historical archives to argue such performance is an act of resistance to the ahistorical neoliberal commodification of queer. LINEAGE: Matchmaking in the Archive and A Wandering Archive is a project initiated by artist and academic E.G. Crichton. In A Wandering Archive, I collaborated with E.G. Crichton to enact lineage intertwining our subjectivities in a public reading of an unpublished manuscript Ruth Reid and Kent Hyde, a Memoir . What does an archive offer as resistance? How can an archive be performed? Performativity such as this project is a model for archival retrieval. This article interrogates an enactment of GLBT history as performance. This article will address the discursive determinants of neoliberalism's demand for an ahistorical positioning of queer sexualities, subsuming sexualities as plurality and thus rendering them benign. LINEAGE: Matchmaking in the Archive and A Wandering Archive exemplifies the intersection of sexualities and creativity as culturally productive sites.